97.7k views
0 votes
Can someone solve -192= -6 (6x - 4) step by step?

1 Answer

5 votes

Answer:

x= 4 2/3 OR 14/3 OR 4.6... –– 4 2/3 and 4.6... are the simplest form.

Explanation:

Your original equation is -192 = -6 (6x - 4):

1. -192 = -6 (6x - 4)

Use distributive property and multiply: -6 x 6x = -36x and -6 x -4 = 24:

2. -192 = -36x + 24

We now move the +24 onto the other side of the equation, -192. Add 24 onto -192 and since we're moving the 24 on the left side of the equation, 24 will removed, so -24 on the right side of the equation:

3. -192 + 24 = -36x + 24 - 24

Divide both sides of the equations by -36 to get "x" by itself:

4. -168 / -36 = -36x / -36

Simplify the fraction of 24/36 by 12:

5. 4 24/36 = 4 2/3 or 14/3 or 4.6... = x

4 2/3, 14/3, 4.6... = x

User John McCollum
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.